2022
DOI: 10.1155/2022/5623462
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Freezing Twice during Assisted Reproductive Technology on Perinatal and Neonatal Outcomes

Abstract: Objective. The aim of this paper was to investigate whether two freeze-thaw cycles before embryo transfer may affect perinatal and neonatal outcomes. Materials and Methods. A total of 8,028 frozen-thawed embryo transfer patients who became pregnant between March 2013 and September 2019 were included. The patients were divided into two groups: the oocyte cryopreservation (OC) group ( N = 96 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…It has been shown that DMSO and EG can induce alterations in DNA methylation and structural changes in the chromatin and DNA double‐strand breaks 86 . These cryoprotectants might affect embryo metabolism, such as protein expression, DNA integrity, and cytoskeletal and nuclear structures 87–90 . A few studies have suggested that CPAs might be linked to epigenetic aberration in oocytes and embryos, and these alterations could be transmitted to future generations 91,92 .…”
Section: Concerns Related To Cryopreservation and Cryoprotectantsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that DMSO and EG can induce alterations in DNA methylation and structural changes in the chromatin and DNA double‐strand breaks 86 . These cryoprotectants might affect embryo metabolism, such as protein expression, DNA integrity, and cytoskeletal and nuclear structures 87–90 . A few studies have suggested that CPAs might be linked to epigenetic aberration in oocytes and embryos, and these alterations could be transmitted to future generations 91,92 .…”
Section: Concerns Related To Cryopreservation and Cryoprotectantsmentioning
confidence: 99%
“…86 These cryoprotectants might affect embryo metabolism, such as protein expression, DNA integrity, and cytoskeletal and nuclear structures. [87][88][89][90] A few studies have suggested that CPAs might be linked to epigenetic aberration in oocytes and embryos, and these alterations could be transmitted to future generations. 91,92 Thus, since cryopreservation has become widely used in ART and other fields such as regenerative and transplantation medicine, it is critical to examine potentially genomic and epigenetic changes associated with the current technique.…”
Section: Concerns Related To Cryopreservation and Cryoprotectantsmentioning
confidence: 99%